Nintedanib plus mFOLFOX6 as second‐line treatment of metastatic, chemorefractory colorectal cancer: The randomised, placebo‐controlled, phase II TRICC‐C study (AIO‐KRK‐0111). Issue 6 (4th October 2020) - Ettrich, Thomas J.; Perkhofer, Lukas; Decker, Thomas; Hofheinz, Ralf‐Dieter; Heinemann, Volker; Hoffmann, Thomas; Hebart, Holger F.; Herrmann, Thomas; Hannig, Carla V.; Büchner‐Steudel, Petra; Güthle, Melanie; Hermann, Patrick C.; et al.
Abstract: Nintedanib is a triple angiokinase inhibitor of vascular endothelial growth factor receptor 1‐3, fibroblast growth factor receptor 1‐3 and platelet‐derived growth factor receptor‐a/‐b. Thereby, it targets angiogenic escape mechanisms. The trial TyRosine kinase Inhibitor for the treatment of Chemorefractory Colorectal Cancer (TRICC‐C) trial evaluates the addition of nintedanib to mFOLFOX6 (fluorouracil, folinic acid and oxaliplatin) in patients with metastatic colorectal cancer (mCRC). TRICC‐C is a randomised controlled, double‐blinded, phase II trial in mCRC patients that received a first‐line non‐oxaliplatin containing chemotherapy. Patients received mFOLFOX6 + nintedanib (F + N) (2 × 200 mg p.o./d, d1‐d14) or mFOLFOX6 + placebo (F + P), in a 1:1 ratio. Primary endpoint was median progression free survival (mPFS) and secondary overall response rate (ORR), overall survival (OS) and safety. Fifty‐three patients (27 F + N; 26 F + P) were randomised between 12/2012 and 5/2016 (scheduled n = 180). The trial was terminated prematurely due to slow accrual. The trial did not reach its primary endpoint but mPFS, median overall survival (mOS) and disease control rate (DCR) were numerically higher in the F + N arm compared to the F + P arm; however, the difference was not significant (mPFS: F + P: 4.6 months vs F + N: 8.1 months; HR 0.65; 95% CI 0.32‐1.30; P = .2156; mOS: F + P: 9.9 months vs F + N: 17.1 months; HR 1.03, 95% CI 0.48‐2.23; P = .9387; DCR: F + P: 50% vs F + N: 66, 7%; P = .2709). Toxicity was moderate and only different for neutropenia (F + P: 11.5%, F + N: 19.2%) and gastrointestinal disorders (F + P: 65.4%, F + N: 84.6%). Final results show safety and a nonsignificant trend towards improved PFS and DCR for the combination of mFOLFOX6 + nintedanib in the second‐line therapy of mCRC. What's new?: Anti‐angiogenic agents frequently are used in combination with fluorouracil‐based doublet chemotherapy for metastatic colorectal cancer (mCRC) following failure of first‐line therapy. Prolonged use of existing angiogenesis inhibitors, however, fuels the development of resistance, necessitating a search for more effective anti‐angiogenic agents. Here, the authors examined the novel angiogenesis inhibitor nintedanib in combination with modified FOLFOX in second‐line treatment of mCRC. Nintedanib plus mFOLFOX was associated with only modest improvements in survival, a result potentially impacted by slow patient accrual in the trial. Adverse events were comparable to other combination therapies for mCRC, indicating general clinical safety for nintedanib plus mFOLFOX.